Results of transthoracic esophagectomy following chemoradiation in locally advanced esophageal cancer - (:unkn) unknown (My University, 2008)
We investigated patients treated with chemoradiation and subsequent esophagectomy. 10 patients were treated between 2004-2007. The chemoradiation regimen was concurrent 46-50 Gy radiation with cisplatin and 5-fluorouracil. Average age was 58 (31-74, 5 females). Clinical stages were T3-4N0-1M0. 9 patients completed the curative or neoadjuvant chemoradiation regimen. Pathologies were squamous cell (n=9) and adenocarcinoma (n=1). All patients underwent esophagectomy via a right thoracic approach, followed by laparotomy and cervical incision. There was no postoperative mortality. 7 patients had complications, 4 of them were major. Postoperative stages were T2N0 (n=3), T3N0 (n=3), T2N1 (n=1) and T3N1 (n=3). One patient died due to local and distant recurrence. Two patients (>70 years) died of non-cancer related causes at 2 and 8 months. Seven patients are alive without disease, 3 of them at 36, 19 and 18 months. Esophageal resection following concurrent chemoradiation is a high risk procedure that can be applied in well selected patients.
Keywords: Concurrent chemoradiation; Esophageal cancer; Squamous cell carcinoma; Transthoracic esophagectomy